2012
DOI: 10.1590/s0034-72802012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic analysis of opacification in Ioflex® hydrophilic acrylic intraocular lenses

Abstract: Five cases of intraocular lens (IOL) opacification in patients implanted with the Mediphacos Ioflex® IOL are described. Clinical data in each case was obtained from the patient's medical record. The five explanted IOLs underwent gross and light microscopic analysis. Selected lenses were processed for further evaluation and multiple sagittal cuts were stained with the alizarin red and von Kossa methods. Light microscope analysis confirmed the presence of deposits on and within the lens, which stained positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We report for the first time cases of late opacification of the Ioflex IOL in Europe, specifically in Czech Republic. Although histochemical and/or surface analyses were not performed, the aspect described here appears consistent with a process of calcification of this lens design (2)(3)(4)8). Gross and light microscopy of the explanted IOLs demonstrated the presence of granular deposits, which were predominantly located on the surface/subsurface of the IOLs, particularly the anterior surface.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We report for the first time cases of late opacification of the Ioflex IOL in Europe, specifically in Czech Republic. Although histochemical and/or surface analyses were not performed, the aspect described here appears consistent with a process of calcification of this lens design (2)(3)(4)8). Gross and light microscopy of the explanted IOLs demonstrated the presence of granular deposits, which were predominantly located on the surface/subsurface of the IOLs, particularly the anterior surface.…”
Section: Discussionsupporting
confidence: 53%
“…Some previous studies have also reported cases of opacification of the Ioflex IOL (2-4, 8). Barra et al (2) reported 7 cases of IOL opacification in Brazilian centers.…”
Section: Discussionmentioning
confidence: 91%
“…; Ventura et al. ). The literature shows that the mean period varies from 16.4 to 35.3 months (Ventura et al.…”
mentioning
confidence: 99%
“…The literature shows that the mean period varies from 16.4 to 35.3 months (Ventura et al. ). In our study, the diagnosis was late postoperatively.…”
mentioning
confidence: 99%
“…Surprisingly similar SEM images were published [14] for a hydrophilic intraocular lens explanted from a patient with injection of intraocular gas. In earlier studies, the patterns of the opacifying deposits are described as characteristic ring-like crystalline structure [14], but also as "cerebriform" pattern [15][16][17][18]. The shape of the grains (Fig.…”
Section: Resultsmentioning
confidence: 99%